EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STRUCTURED NUMBERED HEADS, THINK TALK WRITE, DAN LEARNING TOGETHER DENGAN PENDEKATAN SAINTIFIK DITINJAU DARI KECERDASAN LOGIKA MATEMATIKA SISWA - Utami, Desi Tri; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2015)
Abstract: The purpose of this research was to find out the effect of the cooperative learning models on the learning achievement in mathematics viewed from the students’ logical mathematical intelligence. The learning models compared were the cooperative learning models of Structured Numbered Heads (SNH), Think Talk Write (TTW), and Learning Together (LT) with scientific approach. This research used quasi experimental research method with the factorial design of 3x3. The population of the research was all of the students in grade VII of Junior High School in Sukoharjo Regency. The data was analyzed using two-ways analysis of variance with unbalanced cell. The conclusions of the research were as follows. (1) SNH and TTW with scientific approach had the same learning achievement. SNH and TTW with scientific approach had better learning achievement than LT with scientific approach. (2) Students with high logical mathematical intelligence had better learning achievement than the students with middle and low logical mathematical intelligence, also students who had middle logical mathematical intelligence had better learning achievement than students who had low logical mathematical intelligence. (3) In SNH with scientific approach, the students who had high logical mathematical intelligence had learning achievement as good as students with middle and low logical mathematical intelligence. In TTW and LT with scientific approach, the students who had high logical mathematical intelligence had learning achievement as good as students with middle logical mathematical intelligence, and the students who had high and middle logical mathematical intelligence had better learning achievement than the students with low logical mathematical intelligence. (4) For all level of students’ logical mathematical intelligence, the students who were given by SNH, TTW, and LT with scientific approach had the same learning achievement.Keywords: Structured Numbered Heads, Think Talk Write, Learning Together, Scientific Approach, Logical Mathematical Intelligence